Envision and Appraisal of Biomolecules and Their Interactions through Scanning Probe Microscopy - Prachi Ghoderao; Sanjay Sahare; Shern-Long Lee; Prashant Sonar (Small Structures, 2023)
Scanning probe microscopy (SPM) has gifted a novel eye to envision nanotechnology and nanoscience. The SPM technique involves a sharp probe that moves over the sample surface and leads to produce signals, which facilitates a deep understanding of the structural, electronic, vibrational, optical, magnetic, (bio) chemical, and mechanical properties of the material. Scanning tunneling microscopy (STM) and atomic force microscopy (AFM) measure various kinds of physical properties such as electric current, force, and capacitance. Moreover, AFM shows a prominent feature over STM that it accepts insulating surfaces and can work under physiological conditions, making it feasible to study biological molecules. Herein, the SPM approach toward biomolecule imaging and appraising different physiological processes with molecular resolution is highlighted. The review raises awareness regarding current obstacles in biological sample preparation and possible ways to conquer these difficulties. Subsequently, the recent applications of STM and AFM on various biomolecules with representative examples like DNA, protein, and carbohydrates are discussed. The conductance measurement studies of the biological samples emphasize applications like drug delivery, biosensors, molecular electronics, and spintronics fields. This is followed by an outlook of future perspectives making a pavement toward the basic science and applied field of biomolecules using SPM technology.